THE INFLUENCE OF PRODUCT QUALITY AND DISTRIBUTION ON THE PURCHASING DECISION OF SEMEN BATURAJA - Indra Maulana; Marlina Widiyanti; Muchsin Saggaff Shihab; Zakaria Wahab (SEAN Institute, 2023)
This research aims to determine the influence of product quality and distribution on the purchasing decision of Semen Baturaja. The population in this study is all Baturaja cement consumers who purchased Baturaja Cement in the Lampung region in the 2021 period with the purchase category on 50 kg zak bag packaging as many as 100 respondents. The data collection method uses questionnaires that are distributed to all consumers and the data is processed using multiple linear regression analysis. The results of multiple linear analysis show that product quality and distribution have a positive and significant effect on Baturaja's cement purchasing decisions. Product quality is expected to add types of cement variants not produced by PT Semen Baturaja (Persero), Tbk. With the increasing number of competitors of cement companies in Indonesia, PT Semen Baturaja (Persero), Tbk needs to make many innovations in order to compete. The distribution is expected that PT Semen Baturaja (Persero), Tbk needs to evaluate in order to provide transportation fleets that need to be added. With consumer complaints that say that the length of the distribution process is due to the lack of transportation owned.